Measuring the impact of accounting disclosure and the quality of financial reports through the Sudanese commercial banks' governance mechanism - Abdelrahman Ali, محمد الطيب (Journal of Finance & Corporate Governance, 2021)
The study focused on knowing the impact of accounting disclosure on the quality of financial reports through the application of the banking system’s governance mechanism, and knowing the extent of Sudanese commercial banks ’commitment to implementing the governance mechanism in a manner that achieves banking safety and improves the quality indicators of banking performance, using the deductive approach to define research axes and formulate assumptions. The use of the inductive approach to test the hypotheses to ensure their validity, and the use of the analytical descriptive method to interpret and analyze the field study information using the Statistical Package for Social Sciences (SPSS) program to reach the results. The study concluded that the commitment of Sudanese commercial banks to apply the mechanism and principles of governance or what is known exactly as the institution The Central Bank of Sudan, and thus increasing the level of accounting disclosure, which is reflected in the quality of financial reports, improving the index and quality of the performance of these banks, and the possibility of benefiting from the advantages achieved by governance that support the commitment to apply governance mechanisms to raise the level of accounting disclosure in financial reports, and thus increase the quality of financial reports to banks, and commitment By applying governance mechanisms in the sucking system Sudanese well-being improves performance indicators, whenever mentioned, in addition to trying to benefit from the advantages of governance and supporting commitment to its application in banks, and working to increase awareness of the concept of governance at the professional level, through seminars and training courses for employees of the banking system, and to establish the culture of justice, transparency and fair treatment. Among the various departments of banks and their employees, the need to pay attention to studies and research on the application of good governance in practice and its role in preventing the occurrence of financial crises and avoiding the failure of banks financially.